2018
DOI: 10.1177/1557988318786868
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Relationship Between Body Image Perception, Eating Disorders, and Muscle Dysmorphic Disorders in Male Bodybuilders?

Abstract: Bodybuilding has increasingly become popular between males since male body shape has become a subject of interest in the last decades. Bodybuilders have desired to gain more muscle and paid attention to their body shape. Based on this purpose, they have string rules that include restrictive eating and excessive exercise program. Recent research has demonstrated that desiring more muscular body shape exhibits eating behavior problems and body dissatisfaction issues in bodybuilders. Limited research exists on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 53 publications
3
52
3
3
Order By: Relevance
“…Such findings corroborate those found by Devrim, Bilgic and Hongu [62], who observed some behaviour related to EDs among fitness participants, highlighting that behaviour is directly associated with BD and body dysmorphic disorder. Nevertheless, Lechner et al [63] observed that college students who practiced aerobic exercises (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Such findings corroborate those found by Devrim, Bilgic and Hongu [62], who observed some behaviour related to EDs among fitness participants, highlighting that behaviour is directly associated with BD and body dysmorphic disorder. Nevertheless, Lechner et al [63] observed that college students who practiced aerobic exercises (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…28 The cut-off point of the scale is 39 (minimum 0-maximum 65 points), and scores equal to and greater than 39 reflect strong symptoms of MD. 16 Its reliability and validity studies in our country, Turkey, were carried out by Devrim in 2016, and its Cronbach's α value was found as 0.66. 29,30 In this present study, Cronbach's α value of the scale was determined to be 0.83.…”
Section: Orthorexia Scalementioning
confidence: 99%
“…11,13 Such obsessions with the body can lead to serious clinical disorders, leading to loss of employment, loss of family and friends, or depression, suicide and even death, as well as kidney failure, heart diseases, and damaged self-esteem. [14][15][16] Research has shown that eating disorders and MD show similarities in most ways. 7 Obsession with having more muscle mass in people with MD has been found to cause serious eating disorders at a psychopathological level.…”
Section: Introductionmentioning
confidence: 99%
“…Important risk and trigger factors of poor eating habits in FP athletes may include the focus on aesthetic appearance as the primary performance marker in competition (Sundgot-Borgen and Torstveit, 2004), the peer/media pressure which can elicit body dissatisfaction (Hausenblas et al, 2013) and the influences from coaches with inadequate nutrition knowledge (Sundgot-Borgen, 1994). There is also evidence that FP athletes are particularly vulnerable to DE/ED and body image dissatisfaction because of the preoccupation with being muscular and lean (Devrim et al, 2018).…”
Section: Disordered Eating /Eating Disorders Behavioursmentioning
confidence: 99%